2015
DOI: 10.1021/acsbiomaterials.5b00092
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Process for the Spinning of Synthetic Spider Silk

Abstract: Spider silks have unique mechanical properties but current efforts to duplicate those properties with recombinant proteins have been unsuccessful. This study was designed to develop a single process to spin fibers with excellent and consistent mechanical properties. As-spun fibers produced were brittle, but by stretching the fibers the mechanical properties were greatly improved. A water-dip or water-stretch further increased the strength and elongation of the synthetic spider silk fibers. Given the promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 50 publications
2
89
0
Order By: Relevance
“…Most studies characterizing post-spin stretching of silk-based fibers have reported carrying out this step manually with the use of forceps or tweezers 9,11,12,42 , with some reports of using controlled post-spin stretching apparatuses (e.g. 16,44 ). An apparatus can certainly be envisioned that incorporates the post-spin stretching as part of an automated fiber production process 16,44 .…”
Section: Post-spin Stretching Of As W 3 Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies characterizing post-spin stretching of silk-based fibers have reported carrying out this step manually with the use of forceps or tweezers 9,11,12,42 , with some reports of using controlled post-spin stretching apparatuses (e.g. 16,44 ). An apparatus can certainly be envisioned that incorporates the post-spin stretching as part of an automated fiber production process 16,44 .…”
Section: Post-spin Stretching Of As W 3 Fibersmentioning
confidence: 99%
“…16,44 ). An apparatus can certainly be envisioned that incorporates the post-spin stretching as part of an automated fiber production process 16,44 . However, this requires knowledge of the optimal degree of post-spin stretching.…”
Section: Post-spin Stretching Of As W 3 Fibersmentioning
confidence: 99%
“…34. The production process 35 involved coagulation of a fiber in an IPA bath, passing through a methanol/ water bath where it was stretched 1.5Â, and then through a water bath, where 65 mg of Rhodamine B was dissolved in 200 ml of distilled water, and stretched again 1.5Â. This allowed the Rhodamine B to be integrated throughout the fiber surface, although at an unknown concentration.…”
Section: B Fluorophore Selectionmentioning
confidence: 99%
“…Recently, Copeland et al . prepared synthetic spider silk using a wet-spinning process that involved an air gap32. However, the function of this air gap was not investigated.…”
Section: Resultsmentioning
confidence: 99%